Evaluation of fuelling requirements for core density and divertor heat load control in non-stationary phases of the ITER DT 15 MA baseline scenario. (5th May 2020) - Koechl, F.; Ambrosino, R.; Belo, P.; Cavinato, M.; Corrigan, G.; Garzotti, L.; Harting, D.; Kukushkin, A.; Loarte, A.; Mattei, M.; Militello-Asp, E.; Parail, V.; et al.
Abstract: To ensure optimal plasma performance at high Q fus for the baseline scenario foreseen for ITER, the fuelling requirements, in particular for non-stationary phases, need to be assessed by means of integrated modelling to address the special additional challenges facing plasma fuelling on ITER. The fuelling scheme needs to be adjusted to ensure robust divertor heat load control, avoiding complete detachment while still maintaining low divertor temperatures and heat fluxes to minimise W sputtering and contamination of the plasma by impurities. At the same time, the core density needs to be controlled to fulfil requirements for: the application of neutral beam heating with acceptable shine-through losses; a robust transition from L-mode to stationary fusion burn; the maximisation of the fusion yield; and a fast reduction in core particle content in the termination phase. Coupled core-edge-SOL transport calculations have been performed, simulating for the first time the entire ITER plasma evolution from just after the X-point formation until the late termination phase. These calculations are being exploited to find the most effective ways of fuelling and heating DT plasmas without exceeding ITER operational limits (e.g. divertor power density). The most efficient ways to fuel ITER with gas and/or pellet injection have been investigated self-consistently with the integrated core + edge + SOL transport suite of codes, JINTRAC, developed at JET (Romanelli et al 2014 Plasma Fusion Res. 9 3403023). Our modelling is exploited to study schemes for gas and pellet fuelling for main ion SOL and core density control, respectively, and for impurity seeding by Ne for the control of SOL radiation, that allow ITER to approach Q fus ∼ 10, with plasma evolution successfully controlled to respect major operational limits through all transients from the early ramp-up until the late ramp down phase.